LANDSLIDE PROTECTION STRUCTURE IN THE FORM OF COUNTERFORTS MADE OF BORED PILES (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
At present, we are witnessing an intensive urbanization which is also typical for most regions of Ukraine. As consequence, there is an increase in the anthropogenic pressure on certain territories that’s why the problem of the development of such phenomena as landslides has become particularly relevant. The landslides are one of the most common exogenous geological processes creating environmental and technogenic hazards. The reasons for their activation can be divided into natural and man-made. The landslide processes of natural origin arise, as a rule, on the coast, on the slopes of river valleys and in the network of gullies and ravines. The technogenic landslides are observed in the construction sector, reconstruction and operation of buildings and structures built on a plot of slopes with difficult engineering and geological conditions. With the aim of preventing the occurrence of landslides and related emergencies of a man-made and natural nature, it is necessary to implement economically and environmentally sound anti-landslide measures before the start of economic development of landslide and landslide hazard areas. In building on landslide and landslide hazard slopes or on artificial slopes, it is necessary to keep large masses of soil in stable state. The occurrence and activation of landslides leads to the formation of unacceptable deformations, disruption of the slope stability as well as the destruction of buildings and structures. The deformations of buildings and structures located on or near slopes occur from landslide processes that cannot be stopped by regular landslide prevention works. In these cases, retaining anti-landslide structures made of bored and cast-in-place piles embedding in stable bedrocks and combined with reinforced concrete grille are used to protect against the formation of landslides. Such structures are one of the most optimal, technological and cost-effective methods for stabilizing landslide dislocations. The choice of the anti-landslide retaining structures type and their location on the slope depends on the value of the shear stress and its distribution along the slope, the power of the shear rock mass, the configuration of the slope, the state of shear at the time of building and other factors.In this work, the main existing structures of transverse and longitudinal retaining pile-type anti-landslide structures, their advantages and disadvantages, conditions of application were analyzed. As a result of this, a new design retaining anti-landslide structure with increased loadability and reduced consumption of materials has been proposed. The landslide protection structure is made in the form of the counterforts run parallel to the length of the shear slope formed of round bored piles, whose diameter increases in the direction of shear displacement. While, the piles are laid with their lower ends in firm grounds and combined from above with reinforced concrete grille of variable height with an inclination of the bottom surface towards base of slope. This structure is designed to stabilize landslide hazard and landslide slopes as well as to increase stability of the slopes plots on which buildings and structures for various purposes are operated, reconstructed and built.